2009
DOI: 10.1167/iovs.08-1942
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability and Gait among Older Adults with Age-Related Maculopathy

Abstract: Impaired contrast sensitivity was associated with postural instability, slower walking velocity, increased step width, and reduced stride length. Impairments in either contrast sensitivity or visual fields were associated with increased double-support time. This result suggests that loss of contrast sensitivity and visual fields in patients with ARM can lead to balance and mobility problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
66
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 26 publications
8
66
2
Order By: Relevance
“…46 A recent investigation of patients with age-related maculopathy assessed postural stability and gait to try to identify the visual factors responsible for any deficits. 49 The results suggested that all visual factors but particularly reduced contrast sensitivity were associated with postural instability and changes in gait after adjustment for age, sex, self-reported physical function and cataract severity.…”
Section: Age-related Macular Degeneration and Fallsmentioning
confidence: 87%
“…46 A recent investigation of patients with age-related maculopathy assessed postural stability and gait to try to identify the visual factors responsible for any deficits. 49 The results suggested that all visual factors but particularly reduced contrast sensitivity were associated with postural instability and changes in gait after adjustment for age, sex, self-reported physical function and cataract severity.…”
Section: Age-related Macular Degeneration and Fallsmentioning
confidence: 87%
“…Visual information contributes considerably to the control of bipedal stance; e.g., poor or absent visual input has a detrimental effect on postural stability (Allum and Pfaltz 1985;Fitzpatrick et al 1992;Simoneau et al 1992;Schumann et al 1995;Wood et al 2009) and manipulation of the visual environment mimicking motion of the visual environment can induce changes to the dynamics of postural sway (Lee and Lishman 1975;Schöner 1991;Dijkstra et al 1994a, b;Polastri and Barela 2013;Barela et al 2014). In the absence of vision, intermuscular coherence at 0-5 Hz between bilateral leg muscles was reduced during quiet standing (Boonstra et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both these studies however, use gait measures which contain additional components of kinematic performance, for example, turning or physical endurance. Poorer CS, as measured using the Pelli-Robson test, has been independently associated with slower gait speed, shorter stride length, wider step width, increased double support time (10) and failure on the Buck Center Walking Test (14).…”
mentioning
confidence: 99%
“…Some studies report no independent association between VA and common gait measures, that is, gait speed, cadence, and stride length (9)(10)(11)(12). However, one large study (n = 5,143) of older adults (age >70 years) notes that severe impairment in VA, after adjusting for age and gender, is associated with an inability to complete an 8-foot walk test (13).…”
mentioning
confidence: 99%